Family farming in Mozambique: Characteristics and challenges (Research, Society and Development, 2021)
The article aims to present the role and challenges of family farming in Mozambique. The study used articles, downloaded from Google Scholar published between 2000 - 2020, books, reports and dissertations addressing topics on agriculture, rural development and food security. The analyses suggest that family farming is practiced by the majority of the Mozambican rural population and is mainly for subsistence, characterized by strong dependence on nature and poor use of technologies. In general Mozambique faces many challenges for rural development, as many families are still experiencing hardship. Inequalities in access to infrastructure between the southern, central and northern regions and between the urban centers and the rural regions are quite pronounced. The literature review further point out that Mozambique agriculture policies are inconsistent, leaving most farmers without access to basic services and infrastructure that could have an impact on improving their livelihoods. The study suggests that the Mozambican government should create more robust and feasible policies capable of contributing to the promotion of rural development, reducing regional asymmetries and improving the quality of life of rural household.